Eschar removal by bromelain based enzymatic debridement (Nexobrid®) in burns: An European consensus. Issue 8 (December 2017) - Hirche, Christoph; Citterio, Antonella; Hoeksema, Henk; Koller, Ján; Lehner, Martina; Martinez, José Ramón; Monstrey, Stan; Murray, Alexandra; Plock, Jan A.; Sander, Frank; Schulz, Alexandra; Ziegler, Benjamin; et al.
Highlights: User-based recommendations for enzymatic debridement in burns beyond literature. The use of enzymatic debridement benefits from standardized protocols and significant experience. Pseudo-eschar is a specific layer sticking to the wound after enzymatic debridement. Enzymatic debridement should be regarded as a debridement and a strategic tool. Role in mass casualty and right time point of transplantation will benefit from further data. Abstract: Early debridement and/or eschar removal is regarded as a significant step in the treatment of deep partial and full thickness burns. It aims to control wound bioburden and allows early wound closure by conservative treatment or skin grafting. Preservation of viable dermis accompanied by early wound closure, is regarded as a necessary step to reduce scar related complication, e.g. functional limitations and/or unaesthetic scar formation. Aside from the classical techniques of surgical excision as tangential excision for eschar removal, hydro-surgery, maggot therapy, laser, enzymatic debridement have been described as additional techniques in the burn surgeon's armamentarium. It is widely accepted that early eschar removal within 72 h improves the outcome of burn wound treatment by reducing bacterial wound colonization, infection and length of hospital stay. In contrast, the right technique for eschar removal is still a matter of debate. There is increasing evidence that enzymatic debridement is a powerful tool to remove eschar in burn wounds, reducing blood loss, the need for autologous skin grafting and the number of wounds requiring surgical excision. In order to assess the role and clinical advantages of enzymatic debridement by a mixture of proteolytic enzymes enriched in Bromelain (Nexobrid ® ) beyond the scope of the literature and in view of users' experience, a European Consensus Meeting was scheduled. The aim was to provide statements for application, based on the mutual experience of applying enzymatic debridement in more than 500 adult and pediatric patients by the consensus panelists. Issues to be addressed were: indications, pain management and anesthesia, timing of application, technique of application, after-intervention care, skin grafting after enzymatic debridement, blood loss, training strategies and learning curve and areas of future research needs. Sixty-eight (68) consensus statements were provided for the use of enzymatic debridement. The degree of consensus was remarkably high, with a unanimous consensus in 88.2% of statements, and lowest degree of consensus of 70% in only 3 statements. This consensus document may serve as preliminary guideline for the use of enzymatic debridement with user-oriented recommendations until further evidence and systematic guidelines are available.